Molecular detection of plant pathogenic bacteria, Xanthomonas sp. from white kelampayan (Neolamarckia cadamba) using pcr approach - Hasfar Syafiqah, Abdul Ghofar (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Neolamarckia cadamba (Roxb.) Bosser or locally known as white kelampayan is a fast growing plantation tree species with high economic values such as in pharmaceutical industry, wood-based industry and pulp and paper industry. Recently, a genome survey of N. cadamba was conducted by using a genomic DNA isolated from a fresh and healthy leaves tissue of N. cadamba. Part of the genomic sequences showed high similarity with Xanthomonas sp. sequences. Xanthomonas sp. is the plant pathogenic bacteria that infects the extracellular of the plant and results numerous numbers of spots on leaves and fruit surface. Polymerase Chain Reaction (PCR) was performed using an entrobacterial repetitive intergenic consensus (ERIC) sequence-based primer to detect the Xanthomonas sp. sequences. A total of 14 DNA samples ofN. cadamba had been extracted from two geographical distinct locations. Four DNA sample originated from the same geographical location had been detected with the presence of Xanthomonas sp. Based on the cluster analysis, DNA samples of N. cadamba were grouped into two major clusters, suggesting the WI, W2, W3 and W5 DNA samples with the presence of Xanthomonas sp .• to form a single cluster known as cluster I.